2018
DOI: 10.1145/3152891
|View full text |Cite
|
Sign up to set email alerts
|

A Checkpoint of Research on Parallel I/O for High-Performance Computing

Abstract: We present a comprehensive survey on parallel I/O in the high performance computing (HPC) context. This is an important field for HPC because of the historic gap between processing power and storage latencies, which causes applications performance to be impaired when accessing or generating large amounts of data. As the available processing power and amount of data increase, I/O remains a central issue for the scientific community. In this survey, we focus on a traditional I/O stack, with a POSIX parallel file… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 122 publications
(119 reference statements)
0
17
0
2
Order By: Relevance
“…To confirm that it was not something specific to the application, we conducted experiments with the BT-IO benchmark from the NPB [16], the second most used benchmark in the parallel I/O research field, as pointed by [17]. We used the D class, which generates a file of approximately 132.6 GB and yields an execution time in order of minutes.…”
Section: A Experiments With the Bt-io Benchmarkmentioning
confidence: 99%
“…To confirm that it was not something specific to the application, we conducted experiments with the BT-IO benchmark from the NPB [16], the second most used benchmark in the parallel I/O research field, as pointed by [17]. We used the D class, which generates a file of approximately 132.6 GB and yields an execution time in order of minutes.…”
Section: A Experiments With the Bt-io Benchmarkmentioning
confidence: 99%
“…It is possible to observe that the applications running in SDumont are mostly performing write operations in greater sizes than the observed by related work. Previous studies (Boito et al 2018; Carns et al 2009) already demonstrated that issuing larger requests results in higher I/O performance.…”
Section: Part I—study Of the I/o Workloadmentioning
confidence: 90%
“…例如, 隔离故障节点, 将原来在故障 节点的任务迁移到备份节点, 然后将备份节点加入系统, 恢复系统的正常功能和性能. 检查点技术是 维持程序长时间运行的另一种技术 [94] . 系统周期性地在检查点保存程序执行的现场…”
Section: 热量 使芯片结温保持在很低的水平 有效提升了系统长时间运行的可靠性unclassified